Pengaruh Senam Menopause terhadap Kualitas Tidur Wanita Perimenopause di PMB Rama Agustina - Novi Rida Eriyani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Sleep disturbance is one of the most common complaints experienced by perimenopausal women due to hormonal changes. Menopause exercise is a complementary therapy that may help improve sleep quality through regular physical activity. Objective: To determine the effect of menopause exercise on sleep quality among perimenopausal women at PMB Rama Agustina. Methods: This study employed a quasi-experimental design with a one-group pretest-posttest approach. A total of 30 perimenopausal women were selected using purposive sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). The intervention consisted of menopause exercise conducted for four weeks. Data were analyzed using the Wilcoxon Signed Rank Test. Results: The mean sleep quality score decreased from 10.23 before the intervention to 6.37 after the intervention, with a mean difference of 3.86 points. The Wilcoxon test showed a p-value of 0.000 (p<0.05). Conclusion: Menopause exercise had a significant effect on improving sleep quality among perimenopausal women at PMB Rama Agustina.